2017
DOI: 10.1001/jamainternmed.2017.1136
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Quality Improvement Interventions Designed to Prevent Hospital Readmission

Abstract: IMPORTANCE Quality improvement (QI) interventions can reduce hospital readmission, but little is known about their economic value. OBJECTIVE To systematically review economic evaluations of QI interventions designed to reduce readmissions. DATA SOURCES Databases searched included PubMed, Econlit, the Centre for Reviews & Dissemination Economic Evaluations, New York Academy of Medicine's Grey Literature Report, and Worldcat (January 2004 to July 2016).STUDY SELECTION Dual reviewers selected English-language stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 82 publications
1
70
1
1
Order By: Relevance
“…This may be particularly valuable in many health care settings worldwide where health care resources may be scarce. In those settings, it is of utmost importance that the resources are prudently allocated to patients who need them the most, making it more crucial for accurate positive prediction of readmission . Further research may be useful to study efficiency of a threshold that reasonably maximizes sensitivity along the derivation cohort's ROC curve to achieve higher PPV.…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly valuable in many health care settings worldwide where health care resources may be scarce. In those settings, it is of utmost importance that the resources are prudently allocated to patients who need them the most, making it more crucial for accurate positive prediction of readmission . Further research may be useful to study efficiency of a threshold that reasonably maximizes sensitivity along the derivation cohort's ROC curve to achieve higher PPV.…”
Section: Discussionmentioning
confidence: 99%
“…This cost (between $8.3 billion and $11.5 billion in 2009), if eliminated, would result in savings of $9.9 billion to $13.7 billion (CPI) . The total cost of HAIs is perhaps higher because the costs associated with physicians’ services, home nursing, and other nonhospital costs are excluded from this estimate …”
Section: Categories With Expenditures Not Intended For Carementioning
confidence: 99%
“…17 The total cost of HAIs is perhaps higher because the costs associated with physicians' services, home nursing, and other nonhospital costs are excluded from this estimate. 43…”
Section: Health Care-associated Infections (Hais)mentioning
confidence: 99%
“…6,8 Of these efforts, interventions with a multidisciplinary, multicomponent approach have lowered readmission rates as well as improved patient care, patient adherence, and patient outcomes. [17][18][19][20][21][22][23][24][25] Specific quality improvement strategies that were significantly associated with reduced HF RSRR include a partnership with physicians or area hospitals, increased nursing involvement with medication reconciliation upon patient discharge, prearranged necessary follow-up appointments prior to discharge, providing patient discharge information directly to primary care physicians, and designation of hospital staff to follow-up with patient laboratory tests that return after patient discharge. 18 One study showed that the addition of postdischarge calls by a pharmacist in addition to a nurse discharge advocate resulted in a lower rate of hospital readmission.…”
Section: Introductionmentioning
confidence: 99%